Effect of Blended Learning on The Eleventh Graders' Achievement and Creative Thinking from The EFL Teachers' and Students' Perspectives in Jenin City Schools - Al-karam, Roa'a Sultan Mahmoud (My University, 2025)
This study investigated the effect of blended learning on the eleventh graders' achievement and creative thinking from the EFL teachers' and students' perspectives in Jenin city schools. The students sample included (198) purposively chosen 11th graders and 17 conveniently chosen EFL teachers in Jenin city secondary Schools. A mixed method approach was implemented. The students completed a questionnaire developed for the purpose of the study. The teachers participated in a structured interview. The analysis process was conducted using SPSS for the questionnaire tool data, and thematic analysis was performed to extract data from the interviews. The study results showed that the students believe that blended learning can improve their achievement at a low level and moderately develop their creative thinking skills. Also, the study revealed the in existence of statistically significant differences in the perspectives of 11th graders regarding the role of blended learning in improving their achievement and creative thinking however, mean scores revealed slight differences in both dimensions in favor of female students related to the achievement and creative thinking. Conversely, students enrolled in the literary stream showed believe that blended learning can affect their achievement. Furthermore, scientific streamers think that blended learnings' impact on their creative thinking is higher. For most of the interviewed teachers, blended learning is generally regarded as a promising method that has the potential to improve educational outcomes, though its effectiveness can differ depending on the context and available resources. Some of the interviewed teachers have the same aspiration regarding blended learning improving students' achievement. However, some teachers were skeptical, and some others pointed out that its success is related to other factors. As for the interviewees, they shared some common grounds regarding the effect of blended learning on students' achievement, as some of them didn't think it enhances students' achievement, while others view it as a means for students to skip assignments and chance to make-up excuses to drop out some lessons, negatively affecting students' results, but developing the students' self-learning skills. The study recommended providing advanced training courses for teachers on applying and implementing blended learning in their classrooms and exploring the factors associated with effective blended learning outcomes in EFL classroom critical and creative thinking skills.
أثر استراتيجية التعليم المدمج في تحصيل طلاب الصف الحادي عشر وتفكيرهم الإبداعي من منظور معلمي وطلاب اللغة الإنجليزية كلغة اجنبية في مدارس مدينة جنين